ANALISIS IMPLEMENTASI REVITALISASI PASAR TRADISIONAL IR. SOEKARNO KABUPATEN SUKOHARJO DALAM RANGKA MENINGKATKAN KUALITAS PELAYANAN - HUMAM MUJAHIDIN AR ROSYIDI; Soewanto Adhi; Lusia Astrika (Journal of Politic and Government Studies, 2016)
IMPLEMENTATION OF REVITALIZATION ANALYSIS OFPASAR IR. SOEKARNO KABUPATEN SUKOHARJOIN ORDER TO IMPROVE SERVICE QUALITYABSTRACTResearch on implementation of revitalization analysis of Pasar Ir. Soekarno Kabupaten Sukoharjo in order to Improve Service Quality has the objective to investigate the implementation of the revitalization of Pasar Ir. Soekarno, who had finished as well as knowing the impact to the surrounding environment and society as a form of improving the quality of government services, especially in the traditional market management Ir. Soekarno. In addition Sukoharjo district government also has promised to give priority to the welfare of the traders in order to continue to grow and expand its business despite of many modern shopping malls and shops.This study uses the theory Impementasi policy by Marilee S. Grindle about factors - factors relating to an implementation of a policy and what it has led to the implementation of a policy that worked. In addition, researchers also use the theory of public services by Ibrahim and quality of service by Gaspersz about what led to a policy can have an impact on the quality of government services. The method used in this research is descriptive method qualitative data collection techniques such as interviews, observation and documentation. Informants in this study is the Department of Industry and Trade (Industry and Trade), and the Regional Development Planning Board (Bappeda), Public Works Department (DPU), District Sukoharjo, Head of Traditional Market Ir. Sukarno, the Market Traders Association (HPP) Ir. Soekarno and the traditional market traders Ir. Sukarno as the recipient of the revitalization of the market.Based on research that has been done can be concluded that the implementation of the revitalization of Pasar Ir. Soekarno Kabupaten Sukoharjo has been going well. Regarding the impact on the traditional market services Ir. Soekarno we can know that with the additional facility of traditional markets such as improved security and hygiene, increase the amount of labor, creation of parking areas and open spaces have answered the needs of the traditional market services Ir. Soekarno.Finally, with traditional market research is expected to be chosen by the public to meet all the needs of day - day. So that traders and the public will continue to keep the existence of Pasar Ir. Soekarno.Keywords: Policy Implementation, Revitalization of Traditional Markets, Service Improvement